Climate change and technical optimization: The application of an integrated assessment model to Pakistan / Adeel Ahmed - Adeel, Ahmed (2016)
Climate change is a big threat to Pakistan’s agricultural sector, which is locked in low productivity, low technology, and hence operating below subsistence level. Crop production is expected to fall significantly following from frequent combinations of droughts and rainfall, as the technologically backward sector is unlikely to withstand the pressures of climate change. This begs the question on the optimum level of technical change required to address climate change effects on agricultural production. The principle objectives of the study are summarized herein: first, to identify the effects of climate change on the agriculture sector by decomposing them on crop specific levels; second, to determine the optimum level of technical change (TC) that can mitigate climate damages on agriculture; and third, to estimate the costs and benefits of the investments involved in implementing TC in agriculture and the overall economy. For projecting climate damages on 15 sub-sectors of agriculture, the study employs an integrated approach that combines the economic and ecological dimensions of the Pakistan economy. Using a dynamic Computable General Equilibrium (CGE) model, three scenarios were constructed in order to run simulations on climatic changes for agriculture. They include a baseline scenario with no climate change, a climate change scenario and a TC scenario to account for the mitigating potentials of TC. All economic activities are converted into a common unit, and then calibrated based on the economic data generated from the Social Accounting Matrix (SAM) of Pakistan. The climate parameters include climatic damage, carbon cycle, temperature and rainfall fluctuations, carbon emissions, vulnerability and carbon concentration, which are obtained from a Dynamic Integrated Model of Climate and Economy (DICE), and downscaled to fit in country specific outcomes, with a regional scope. The core findings of the study are as follows. First, climate change exerts a considerable negative impact on the agricultural sector in Pakistan. The magnitude of agricultural damages reflects the vulnerability of the sector. The damages on the sectoral level indicate significant distributional effects across agricultural crops, with expectations of largest economic losses for livestock, a key sub-sector for Pakistan. Second, the analysis reveals that TC moderates the damages incurred from climate changes and leads to steady increases in crop yields for all sub-sectors. More importantly, the study concedes that the costs of TC, though variations across sub-sectors of agriculture, are much lower than the damages imposed by climate change. The results, therefore suggest that an optimum level of TC adaptation is needed to produce net positive gains across sub-sectors. Third, TC has positive macroeconomic implications for the overall economy as it improves the gross domestic product (GDP) of Pakistan following from the rise in agricultural output. Further, based on the welfare criteria, TC is efficient as it improves production along with private consumption. Given the importance of TC for addressing the disproportionate effects of climate damages across the sub-sectors of agriculture, the study provides important implications for resource allocation to the underinvested sector of the economy. Specifically, it provides policy direction for prioritizing investments into sub-sectors of agriculture based on their exposure to climate damages.